Corporate Governance and Corporate Social Responsibility Disclosures: A Comparative Analysis Between Australian and Sri Lankan Market - Pratheepkanth, P.; Balaputhiran, S. (SMART Journal of Business Management Studies, 2023)
This paper aims to investigate the effects of corporate governance and CSR disclosures and how they vary, depending on the level of economic development. 100 Australian (ASX200- listed) firms and 100 Sri Lankan firms provided the study’s comparative data (Colombostock-exchange-listed firms). A quantitative research design, based on secondary data, was used to address the research questions. Using content analysis, CSR disclosure information was culled from annual reports and websites. Multivariate regression was used for data analysis and hypothesis testing. Only three factors like board size, audit committee independence, and firm size, were found to be related to the CSR disclosure index, in both Australian and Sri Lankan companies, according to the regression model’s findings. In Australian companies, board independence was strongly correlated with the degree of CSR disclosure. In Australian and Sri Lankan companies, there was little correlation between CEO duality and disclosure of corporate social responsibility. The results are only applicable to the context of the study, which was restricted to listed Australian and Sri Lankan companies in 2020–2021. The study offers evidence on the connection between corporate governance and the degree of CSR, in the context of a developed and an emerging economy as a comparative study. By concentrating on two different stages of economic development as a research context, the study contributes to the body of existing literature.
Keywords: Corporate Governance; CSR disclosure; Australia; Sri Lanka